The Class Origins of Poles: Ancestral Declarations as an Element of Class Position - Cześnik, Mikołaj (Studia Socjologiczne, 2026)
This article examines declared social origins in Poland as a significant yet underexplored dimension of class position in contemporary society. Social origin is conceptualized not only as a biographical fact referring to the structural position of one’s ancestors but also as a symbolic act of identification with a particular class tradition, rooted in family memory and inherited habitus. The study investigates whether and how Poles use categories of social origin, which types of origins they declare, and what social, cultural, and political consequences accompany these declarations. The empirical analysis draws on data from the 2023 Polish National Election Study (POLNES), based on representative samples of adult residents of Poland. The findings show that declared social origin is strongly associated with other dimensions of class position, including education, occupational status, cultural and social capital, and subjective assessments of social standing. Importantly, social origin retains independent explanatory power even after controlling for conventional socioeconomic indicators. Declared class origins also systematically differentiate ideological orientations and voting preferences, particularly in the cultural and symbolic domain. The article concludes that social origin constitutes a distinct, relational, and historical component of class that complements dominant structural approaches in quantitative class analysis.